Suicide: a systematic review - Sirdifield, Coral (Probation, mental health and criminal justice, 2023)
Prevention of suicide is a priority area within UK Government policy and within the National Probation Service Health and Social Care Strategy 2019–2022. In this chapter, we review what the research evidence tells us about the rates of suicide amongst people under probation supervision in comparison to the general population. Drawing on evidence from a recent systematic review, we then consider what is known about risk factors associated with suicide, including probation-related factors, how probation can offer an important opportunity for intervention and what is known about approaches to reducing suicide amongst people under probation supervision. In particular, this chapter demonstrates the dearth of probation-specific evidence-based studies in this area, and offers some insight into how the current gaps in the literature could be addressed in the future.